Strategi Pengembangan Sumber Daya Manusia dalam Meningkatkan Kinerja Tenaga Pendidik di SMPN 31 Rejang Lebong - Syaiful Bahri; Murni Yanto (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze human resource development strategies to improve the performance of educators at SMPN 31 Rejang Lebong. The research method used was a qualitative approach with descriptive research. Data collection techniques included in-depth interviews, observations, and documentation studies involving the principal, teachers, and school staff. The data obtained were analyzed using the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and conclusion drawing using triangulation techniques to maintain data validity. The results indicate that the human resource development strategies implemented at SMPN 31 Rejang Lebong include internal and external training, mentoring between teachers, improving digital literacy, strengthening soft skills, and implementing a continuous reward and performance evaluation system. These strategies have a positive impact on improving educator performance, as reflected in increased professionalism, discipline, learning creativity, technology utilization, and collaboration among teachers. The study's conclusions indicate that a planned, participatory, and sustainable human resource development strategy can significantly improve educator performance, despite the constraints of limited time, budget, and differences in teacher readiness and digital literacy.   Keywords: Human Resource Development, Teacher Performance, School Strategy, Educators